2011
DOI: 10.1063/1.3624827
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of high quality Cu2ZnSnSe4 thin films

Abstract: Cu2ZnSnSe4 thin films, fabricated on bare or molybdenum coated glass substrates by magnetron sputtering and selenisation, were studied by a range of techniques. Photoluminescence spectra reveal an excitonic peak and two phonon replicas of a donor-acceptor pair (DAP) recombination. Its acceptor and donor ionisation energies are 27 and 7 meV, respectively. This demonstrates that high-quality Cu2ZnSnSe4 thin films can be fabricated. An experimental value for the longitudinal optical phonon energy of 28 meV was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 20 publications
(22 reference statements)
4
69
0
1
Order By: Relevance
“…Our DFT calculations at the level of the local density approximation (LDA) or generalized gradient approximation (GGA) clearly showed that the gap of the selenide should be about 0.5 eV smaller than that of the sulfide. Calculations using hybrid functionals (e.g., HSE [74]) mixed with Hartree-Fock exchange or at the level of many-body perturbation theory (e.g., GW [75]) also confirmed that the band gap of Cu 2 ZnSnSe 4 should be around 1.0, 0.5 eV smaller than that of Cu 2 ZnSnS 4 at 1.5 eV, which is in good agreement with the photoluminescence spectrum and optical absorption spectrum measurements on high-quality samples [16,[76][77][78].…”
Section: Band Structure and Band Gapsupporting
confidence: 61%
“…Our DFT calculations at the level of the local density approximation (LDA) or generalized gradient approximation (GGA) clearly showed that the gap of the selenide should be about 0.5 eV smaller than that of the sulfide. Calculations using hybrid functionals (e.g., HSE [74]) mixed with Hartree-Fock exchange or at the level of many-body perturbation theory (e.g., GW [75]) also confirmed that the band gap of Cu 2 ZnSnSe 4 should be around 1.0, 0.5 eV smaller than that of Cu 2 ZnSnS 4 at 1.5 eV, which is in good agreement with the photoluminescence spectrum and optical absorption spectrum measurements on high-quality samples [16,[76][77][78].…”
Section: Band Structure and Band Gapsupporting
confidence: 61%
“…There is therefore a high demand for semiconductor compounds for solar cell absorber layers containing low cost, non-toxic, and easy to mine elements with high world reserves. A prime candidate for this is Cu 2 ZnSn(SSe) 4 , which is a further development of CuInSe 2 where rare and expensive In/Ga are substituted with cheap and abundant Zn and Sn, alternating in the lattice on the indium site of the chalcopyrite structure [3,4]. However the complexity of this compound could be too challenging due to a very narrow single phase region in its phase diagram resulting in a variety of secondary phases present in the material [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the advantage of a direct energy band gap (0.9-1.5 eV), 1) high absorption coefficient (>10 4 cm −1 in the visible region) and potential low-cost production, Cu 2 ZnSn(S,Se) 4 (CZTSSe) is a promising thin film photovoltaic (PV) material experiencing rapid progress in recent years.…”
Section: Introductionmentioning
confidence: 99%